Integrating legumes to enhance cereal production: The relative inputs of fertiliser nitrogen and legume biological nitrogen fixation in major wheat and maize producing countries - Mark B. Peoples; Xiaoxi Li; John A. Kirkegaard; Roger D. Armstrong; Ignacio A. Ciampitti; Angelinus C. Franke; Ken E. Giller; James R. Hunt; Marie-Hélène Jeuffroy; Jagdish K. Ladha; Gilles Lemaire; Long Li; et al. (Plant and Soil, 2026)
Background Cereal crops dominate arable agriculture and underpin global food supply. Cereal grain yield is closely related to crop nitrogen (N) uptake. However, excessive inputs of N fertiliser in cereal production systems can have negative environmental consequences and represent high financial risk for farmers. Scope This review explores opportunities to reduce the current reliance of the global staples, wheat ( Triticum aestivum ) and maize ( Zea mays ), on N fertiliser by diversifying cereal-based cropping systems with legumes, in both time (rotation) and space (via intercropping). Increases in cereal grain yield and N uptake resulting from the inclusion of legumes in wheat and maize cropping systems are examined across different geographic regions. The role of grain legumes and legume-based forages, cover-crops and green manures is described for the 15 countries responsible for producing > 70% of the world’s wheat and maize and consuming > 80% of the global applications of N fertiliser to these two cereals. Estimates of the contributions from biological N 2 fixation and legume residual N to cropping soils are provided for individual countries and compared to the N offtake in wheat and maize grain and the quantities of N fertiliser applied. The potential increased area of legumes required for the returns of legume N to match the current amounts of N removed in grain or supplied as fertiliser is assessed for each country, and the strategies that might be necessary to encourage farmers to increase the frequency of legumes used in cereal-dominated cropping systems are outlined.

Correction to: Quantifying country-to-global scale nitrogen fixation for grain legumes. I. Reliance on nitrogen fixation of soybean, groundnut and pulses - Mark B. Peoples; Ken E. Giller; Erik S. Jensen; David F. Herridge (Plant and Soil, 2024)

Quantifying country-to-global scale nitrogen fixation for grain legumes II. Coefficients, templates and estimates for soybean, groundnut and pulses - David F. Herridge; Ken E. Giller; Erik S. Jensen; Mark B. Peoples (Plant and Soil, 2022)

Quantifying country-to-global scale nitrogen fixation for grain legumes: I. Reliance on nitrogen fixation of soybean, groundnut and pulses - Mark B. Peoples; Ken E. Giller; Erik S. Jensen; David F. Herridge (Plant and Soil, 2021)

Reliable quantification of N2 fixation by non-legumes remains problematic - Murray Unkovich; David Herridge; Euan K. James; Ken Giller; Mark B. Peoples (Nutrient Cycling in Agroecosystems, 2020)

Enhanced biological N2 fixation and yield of faba bean (Vicia faba L.) in an acid soil following biochar addition: dissection of causal mechanisms - Lukas Van Zwieten; Terry Rose; David Herridge; Stephen Kimber; Josh Rust; Annette Cowie; Stephen Morris (Plant and Soil, 2015)

Naturalised populations of mesorhizobia in chickpea (Cicer arietinum L.) cropping soils: effects on nodule occupancy and productivity of commercial chickpea - Natalie V Elias; David F Herridge (Plant and Soil, 2015)

Rhizobial counts in peat inoculants vary amongst legume inoculant groups at manufacture and with storage: implications for quality standards - David F. Herridge; Elizabeth Hartley; L. Greg Gemell (Plant and Soil, 2014)

Influence of source and quality of plant residues on emissions of N2O and CO2 from a fertile, acidic Black Vertisol - Nazma Begum; Chris Guppy; David Herridge; Graeme Schwenke (Biology and Fertility of Soils, 2014)

Global inputs of biological nitrogen fixation in agricultural systems - David F. Herridge; Mark B. Peoples; Robert M. Boddey (Plant and Soil, 2008)

Quantifying below-ground nitrogen of legumes - W Dil F. Khan; Mark B. Peoples; David F. Herridge (Plant and Soil, 2002)

Quantifying below-ground nitrogen of legumes. 2. A comparison of 15N and non isotopic methods - Dil F. Khan; Mark B. Peoples; Phillip M. Chalk; David F. Herridge (Plant and Soil, 2002)

Timing of xylem sampling for ureide analysis of nitrogen fixation - David F. Herridge; Mark B. Peoples (Plant and Soil, 2002)